Asian/Pacific Librarians Career Choices: A Mixed Method Study - 周堅中(Jian-Zhong Zhou); 周格蘭(Glen Zhou); 周陽蘭(Allan Zhou); 周米蘭(Mi-Lan Zhou) (Tʻu shu kuan hsüeh yü tzŭ hsün kʻo hsüeh, 2015)
This is a mixed method study of Asian/Pacific librarians career choices related to leadership positions. The statistical analyses are based on data from 91 librarians in survey Q1 distributed to 600+ CALA and APALA members. The correlation, prediction of association, cross-tabbing,and ANOVA tests were applied to the survey.The result shows that the leadership position is correlated with number of years worked in the library profession, number of publications,number of voluntary job changes, and national professional association’s involvement. There was a suggested correlation between leadership positions and additional advanced degrees and over half of librarians with a doctoral degree are in chief librarian positions. The study also nullifies the hypothesis that achieving leadership position is less likely for first generation immigrants or immigrants who did not receive k-12 or undergraduate education in the North America.In addition, the differences in professional,community, and political involvement are examined among professional librarians,supervising librarians and chief librarians.The comments from the quantitative survey Q1 contain rich data which can’t be interpreted by existing statistical methods. The Q1 comments became the first section of a follow-up qualitative study using situation coding and subject perspective coding method. A separate qualitative survey Q2 was sent to 12 Asian/Pacific chief librarians only. Eight chief librarians completed Q2 covering biographical information and in-depth questions on perceptions of leadership achievement gap among Asian/Pacific American ibrarians. Comparison of comments of Q1for professional librarians and Q2 for chief librarians suggested many similar themes emerged. The triangulation from different Asian/Pacific librarian population validated the finding.